On Solutions to Fractional Discrete Systems with Sequential h-Differences - Małgorzata Wyrwas; Dorota Mozyrska; Ewa Girejko (Abstract and Applied Analysis)
We study the subject of a behaviour of the solutions of systems with sequential fractional h-differences. We give formulas for the unique solutions to initial value problems for systems in linear and semilinear cases. Moreover, the sufficient condition that guaranties the positivity of considered systems is presented.